The Effect of Product Quality and Brand Ambassador on Purchase Decision Through Brand Trust as a Mediating Variable for Users of Ms. Glow Skincare Products in Malang City - Fatmala, Fila Dia Ayu; Sudarmiatin; Wening Patmi Rahayu (International Journal of Technology and Education Research, 2025)
This study aims to determine the effect of quality, purchase decision, from product quality and brand ambassadors on purchase decisions with brand trust as a mediating variable for consumers of Ms Glow skincare products in Malang City. This research is important because there are research gaps in previous studies. This study uses nonprobability sampling technique with purposive sampling method. The data collection technique used a questionnaire distributed to respondents with a 5-point Likert scale answer. The sample in this study amounted to 385 respondents with data analysis using the SEM-PLS method SmartPLS4 software. The empirical test results show the research findings, namely that there is a positive and significant influence between product quality on brand trust, there is a positive and significant influence between brand ambassadors on brand trust, there is a positive and significant influence between product quality on purchase decisions, there is a positive and insignificant influence between brand ambassadors on purchase decisions, there is a positive and significant influence between brand trust on purchase decisions through brand trust, and there is a positive and significant influence between brand ambassadors on purchase decisions through brand trust. This study shows that the product quality of Ms Glow skincare products can increase sales and maintain consumer confidence in the quality of products that are no longer in doubt. Therefore, marketers of Ms Glow skincare products must continue to maintain the quality of Ms Glow skincare products to maintain consumer trust and purchasing power.